2013
DOI: 10.1371/journal.pone.0071643
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Acts as an Immunoregulator in the Mouse Brain by Reducing the Incidence of Severe Disease Following Japanese Encephalitis Virus Infection

Abstract: Japanese encephalitis virus (JEV) causes acute central nervous system (CNS) disease in humans, in whom the clinical symptoms vary from febrile illness to meningitis and encephalitis. However, the mechanism of severe encephalitis has not been fully elucidated. In this study, using a mouse model, we investigated the pathogenetic mechanisms that correlate with fatal JEV infection. Following extraneural infection with the JaOArS982 strain of JEV, infected mice exhibited clinical signs ranging from mild to fatal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 65 publications
4
48
0
Order By: Relevance
“…Viral loads in the brain were also compared as previously shown (8,12). Unexpectedly, S982_I A23 F A113 D B81 showed survival curves similar to that of the parent S982-IC virus (Fig.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Viral loads in the brain were also compared as previously shown (8,12). Unexpectedly, S982_I A23 F A113 D B81 showed survival curves similar to that of the parent S982-IC virus (Fig.…”
mentioning
confidence: 64%
“…Several viral and host factors affect disease severity during JEV infection. We previously suggested that the host response, resulting in immunopathological effects, contributes to fatal infections (8). Furthermore, we also demonstrated that the JaOArS982 and JaTH160 strains of JEV exhibited different virulence in mice (8).…”
mentioning
confidence: 66%
See 3 more Smart Citations